9(1-2x)+12(x-3)=7-2(9-5x)

Simple and best practice solution for 9(1-2x)+12(x-3)=7-2(9-5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(1-2x)+12(x-3)=7-2(9-5x) equation:



9(1-2x)+12(x-3)=7-2(9-5x)
We move all terms to the left:
9(1-2x)+12(x-3)-(7-2(9-5x))=0
We add all the numbers together, and all the variables
9(-2x+1)+12(x-3)-(7-2(-5x+9))=0
We multiply parentheses
-18x+12x-(7-2(-5x+9))+9-36=0
We calculate terms in parentheses: -(7-2(-5x+9)), so:
7-2(-5x+9)
determiningTheFunctionDomain -2(-5x+9)+7
We multiply parentheses
10x-18+7
We add all the numbers together, and all the variables
10x-11
Back to the equation:
-(10x-11)
We add all the numbers together, and all the variables
-6x-(10x-11)-27=0
We get rid of parentheses
-6x-10x+11-27=0
We add all the numbers together, and all the variables
-16x-16=0
We move all terms containing x to the left, all other terms to the right
-16x=16
x=16/-16
x=-1

See similar equations:

| 7(x+1)-2(3-2x)=9+3x | | 0,5(x-2)=1-(0,2x+1) | | 44÷12+x÷6=4x÷3 | | 2x+16=300 | | 6t+5/7=5 | | 6x-193x+10=180 | | 26-x=-13 | | x÷7=20 | | (x-2)(x+1)=1/2 | | 2f+9=10 | | -2x+x=23 | | -12+8(x-5)=-4+3(5x-2) | | 4,5y=2,5y+14 | | 5r+5=-10 | | 2x-130=0 | | 2,5x=-27,5 | | 2x^2+100-150=0 | | 3x-2/11=2 | | x^2+100-150=0 | | 5+3×n=12 | | (2x/3)+((9x+2)/6)=x/2 | | 3(x-2)x(x-2)=507 | | 3y-16=214 | | 11=1/2(4z-6+6z+8) | | 10x+24x+14=0 | | x+0.08x=20000 | | -12x^2-28x=0 | | 5x^2-80x+288=0 | | 4(3x+6)=-42+6 | | (4x+1)x(7x-3)=0 | | 2x+13=6x+17 | | 5x^2+80x+288=0 |

Equations solver categories